Presence of the Rights-based Approach in the integral professional training of the SENA-Tunja, Boyacá - Hurtado, Lida Constanza
This study is developed in the context of training for work and human development, it aims to identify the presence of content with a Human Rights Approach in the Pedagogical Model of Integral Vocational Training and in the Institutional Educational Project of the SENA, from the qualitative approach and through content analysis; looking for a diagnosis that allows to implement pedagogical strategies for instructors, from the Human Rights approach, as education and empowerment tools.